Environmental Themes in North Sumatran Literature (2010 - 2022) for Language Education - Wuriyani, Elly Prihasti; Anggreini, Heny; Siallagan, Lasenna; Tansliova, Lili (JOLLT Journal of Languages and Language Teaching, 2025)
This article reviews environmental damage as depicted in literary works by North Sumatran authors between 2010 and 2022, focusing on damage caused by natural phenomena. Using a literary ecocriticism framework and a qualitative descriptive method, the study explores how literature reflects environmental concerns. From 25 works analyzed, 7 literary pieces explicitly address ecological degradation, such as Kampung Medan by Afrion (2011), Pincalang by Idris Pasaribu (2012), Langsam by Nani Tandjung (2016), and Young Woman in a Luxury Hotel by Hamsad Rangkuti (2016). The findings indicate that these authors show increasing ecological awareness by portraying themes of nature’s beauty, its vulnerability, and the human role in environmental destruction through illegal logging, uncontrolled development, and low ecological awareness. The study concludes that these literary works not only serve as educational and entertainment media but also act as critical reflections and offer solutions, including environmental conservation, sustainable resource management, and fostering human-nature harmony, which can be integrated into language and literature education.